Professional Coordination in Cases of Child Maltreatment: Challenging Issues in Estonia, Finland, Slovenia and Spain. a Comparative Study - Järvenpää, Elina; Sandra Martínez-Molina; Jorge Garcés Ferrer; Barbara Haage; Mand, Mari-Liis; Res, Špela (European Journal of Social Science Education and Research, 2018)
Child maltreatment can be considered as a general term that includes not only what is usually considered overt violence, but all forms of actions and neglect that have a negative impact on the child. When investigating cases of child maltreatment, various kinds of professionals are involved, including ones from the child protection authority, education and healthcare system and judiciary. To make sure that no child in need of assistance would go unnoticed and without help, the skill of co-operating is of high importance. Thus, changing of information between specialists is crucial to recognize the victims at early stage and gather as much information as possible to get the full picture of the situation. To this end, this paper analyses the situation in Estonia, Finland, Slovenia and Spain related to professionals’ coordination challenges. Different methodology and instruments have been used such as desk research, focus groups, interviews and questionnaires to get an overview of the process in each country when child maltreatment cases are investigated. According to the results of the analyses, the main problems and areas which need improvement are quite similar in every country. Professionals intervening at a relatively late stage, the lack of time to co-operate and to discuss as well as and the lack of trust with other professionals can be regarded as the biggest problems in co-operation.